Reducing manufacturing costs: the dynamic tolerance system. Issue 1 (1st January 2019) - Lorenzoni, Anselm; Tielemann, Christopher; Sauer, Alexander
Abstract: Can tolerance limits in production be extended without violating the specifications of design and development? Adherence to tolerances is crucial for the technical quality of a manufactured good. Fit functions of modules often involve highly precise tolerances, incurring high costs. To avoid or at least reduce these costs, this paper develops a new approach to tolerances, the Dynamic Tolerance System. This approach allows the manufacturer to expand the tolerance limits of single parts of an assembly group and enables the production of assembly groups that are subject to specific fit functions. Thereby, the Dynamic Tolerance System does not intervene in the design process, does not require expensive machines or error-prone control-loops, and does not use complex assembly procedures. Rather, it relies on modern measurement systems and the infrastructure already developed and deployed within the framework of Industry 4.0 to extend tolerance limits in production without violating the designer's specifications.